Escherichia coli Heat-Labile Enterotoxin B Limits T Cells Activation by Promoting Immature Dendritic Cells and Enhancing Regulatory T Cell Function - Bignon, Alexandre; Watt, Alan P.; Linterman, Michelle A. (Frontiers in Immunology, 2017)
Treatments to limit T cell activation are essential for managing autoimmune and inflammatory disorders. The B subunit of Escherichia coli heat labile enterotoxin (EtxB) is known to ameliorate inflammatory disease in vivo but the mechanism by which this is mediated is not well understood. Here, we show that following intranasal administration, EtxB acts on two key cellular regulators of T cell activation: regulatory T cells and dendritic cells. EtxB enhances the proliferation of lung regulatory T cells and doubles their suppressive function, likely through an increase in expression of the Treg effector molecule CTLA-4. EtxB supports the generation of IL-10-producing dendritic cells that are unable to activate T cells. These data show, for the first time, that mucosal EtxB treatment limits T cells activation by acting jointly on two distinct types of immune cells.